Responsible Procurement of AI Applications: A Risk-Based Framework for Malaysian Government Agencies - David Lau Keat; Ganthan Narayana Samy; Fiza Abdul Rahim; Mahiswaran Selvanathan; Nurazean Maarop; Mugilraj Radha Krishnan; Sundresan Perumal (UITM Press, 2026)
Indexed by MyCite